Molecular Docking Insights into EDTA and Tween-20-Induced Inhibition of Lysozyme in Bacterial DNA Isolation Buffers - Ika Keumala Fitri; Meredith Jannaatu 'Adn; Tegar Cahya Widodo; Muktiningsih Nurjayadi; Futi Kusuma Hati (Program Studi Kimia Universitas Negeri Jakarta, 2026)
The efficiency of bacterial deoxyribonucleic acid (DNA) isolation is a critical bottleneck in Polymerase Chain Reaction (PCR) based pathogen detection. This study investigates the potential inhibitory effects of standard lysis buffer components, including ethylenediaminetetraacetic acid (EDTA), Tris base, and Tween-20, on Hen Egg White Lysozyme (HEWL) to address the low DNA yields observed in a locally developed isolation kit. Molecular docking simulations were performed using AutoDock 4.2.6. The protocol was validated by redocking the native ligand, which established the suitability of a 60x60x60 Å grid box. The results revealed that EDTA binds with high affinity, with an intermolecular energy of -6.44 kcal/mol, and interacts with crucial anchoring residues Trp62 and Asp101. Notably, the hydrophobic tail of Tween-20 exhibited the strongest binding (-7.12 kcal/mol), penetrating the active cleft and blocking the catalytic residue Glu35. Conversely, Tris base and the hydrophilic head of Tween-20 showed weaker, less stable interactions. These findings suggest a dual-inhibition mechanism in which EDTA blocks substrate access, while Tween-20 hinders the catalytic center. This study provides a molecular explanation for the kit's reduced performance and highlights the need for buffer optimization.